Seroprevalence of PCV2 in north eastern hill states of India - RAJESH, J B; RAJKHOWA, S; DIMRI, U; PRASAD, H; PEGU, S R; SAIKIA, P; CHETHAN, G E; ZOSANGPUII, ZOSANGPUII; CHOUDHURY, M; AJITH, Y (The Indian Journal of Animal Sciences, 2019)
This study describe the seroprevalence of porcine circovirus type 2 (PCV2) in north eastern hill (NEH) states of India. Information on PCV2 from NEH states is lacking. Serum samples (306) were collected from the pigs and different epidemiological parameters like age, sex, and litter size of drift or sounder, system of rearing and different clinical symptoms from November 2017 to May 2018. Samples were screened for PCV2 infection by commercially available ELISA kit (INGEZIM PCV IgG and INGEZIM PCV IgM, Ingenasa, Madrid, Spain). Out of 306 serum samples tested, 151 samples were positive for PCV2 infection. An overall PCV2 prevalence of 49.35% was recorded in NEH states of India. Highest prevalence was found in Sikkim (94%) and lowest prevalence in Nagaland (4%). This study revealed that PCV2 is prevalent in all the north eastern states of India which necessitates the need for implementation of prevention and control measures.